The Effectiveness of Learning Media Folklore Text of North Sumatera Based on Blended Learning by 10th Grade Students of Vocational High SchoolHarapan Mekar-1 Medan - Tri Indah Prasasti; Mutsyuhito Solin; Wisman Hadi (BIRCU, 2019)
The aim of the study is to find out the effectiveness of learning media folklore text of North Sumatra based on blended learning. This study used research and development of learning media based on blended learning takes the form of online, offline and face-to-face learning media. The result of the study Learning outcomes in the folklore text material of 10th Grade students of Vocational High School Harapan Mekar-1 Medan after using learning media based on blended learning are in the category of